Frontispiece: Colorimetric Solvent Indicators Based on Nafion Membranes Incorporating Nickel(II)‐Chelate Complexes. Issue 46 (10th November 2014) - Hosokawa, Hitoshi; Funasako, Yusuke; Mochida, Tomoyuki
<x xml:space="preserve">Abstract</x> Solvent‐Indicator Films Films that exhibit color changes in response to organic solvents enable visual recognition of solvents without any analytical instruments. In their Full Paper on page 15014 ff., T. Mochida et al. report colorimetric solvent indicator films that are robust, convenient, and reusable. The films were prepared by incorporating solvatochromic cationic nickel(II) chelate complexes into Nafion membranes. Immersion of the films in solvents effects color changes from red to pale blue green, depending on the donor number of the solvents.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>